Secretion of middle ear in infants - Occurrence, recurrence and related factors - Saes, Sandra de Oliveira; Goldberg, Tamara Beres Lederer [UNESP]; Montovani, Jair Cortez [UNESP] (Fundacao Sociedade Brasileira de Pediatria, 2005)
Objective: The present study aimed at evaluating the occurrence and recurrence of middle ear effusion and possible associated factors in the first two years of life of 190 newborns and infants, participants in the interdisciplinary prevention, detection, and intervention program at the Clínica de Educação para Saúde of Universidade do Sagrado Coração, Methods: Newborns and infants were monthly submitted to anamneses, otoscopy, behavioral hearing assessment using sound instruments and pure tones (pediatric audiometry) and tympanometry. Results: The results revealed that 68.4% of infants presented one or more episodes of middle ear effusion during their two first years, with more recurrence among males. Peak occurrence was between four and 12 months of age and, the earlier the first episode, the higher the probability of recurrence. Greatest incidence was during May and August. It was found that, of the variables investigated, the period of exclusive breastfeeding actuated as a protector factor. With respect of risk factors, it was observed that passive smoking, gastro-esophageal reflux and respiratory allergy were related with the recurrences of effusion. Conclusion: Findings revealed the importance of periodic auditory follow-up for infants during their first two years of life, considered to be the critical period of auditory system maturation, during which sensory deprivation can be responsible for damage to the development of speech, language and other auditory abilities. Copyright © 2005 by Sociedade Brasileira de Pediatria.
Keywords: Acoustic impedance tests; Otitis media; Otoscopy; anamnesis; audiometry; breast feeding; controlled study; female; gastroesophageal reflux; human; infant; major clinical study; male; middle ear effusion; newborn; otoscopy; passive smoking; recurrent disease; respiratory tract allergy; risk factor; tympanometry; acoustic impedance; Brazil; longitudinal study; middle ear; secretion; secretory otitis media; sex ratio; Acoustic Impedance Tests; Breast Feeding; Ear, Middle; Female; Humans; Infant; Infant, Newborn; Longitudinal Studies; Male; Otitis Media with Effusion; Recurrence; Risk Factors; Sex Distribution